The Principles of banking - Choudhry, Moorad; John Cummins;Ian Plenderleith (New Jersey : John Wiley & Son, Inc., 2012)
This banking handbook omits a lot of product detail and complex mathematics on the more technical aspects of finance and focuses on key issues in bank strategy, liquidity management, management reporting, the yield curve and asset liability management
Part I. A Primer on Banking -- Part II. Bank Asset and Liability Management -- Part III. Bank Liquidity Risk Management -- Part IV. Bank Strategy and Governance -- Part V. Applications Software, Policy, Templates and Teaching Aids .
Includes index.
Keywords: BANKS